Comparative Account of Biochemical Analysis of Katelysia opima Along Mumbai Coast, India - Maurya, Shivani; B.M., Gore (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present study aimed to analyze the biochemical composition of Katelysia opima, and compare it with the Tilapia Mossambica and Mystus vittatus. Katelysia opima is a common bivalve rich in protein, serving as a major nutritional source for people. Protein analysis revealed a protein amount of 12.4% in Katelysia opima, while Tilapia mossambica and Mystus vittatus exhibited 13.76 % and 12.85%, protein content respectively. Additionally, lipid content was found to be significantly higher in Katelysia opima (4%) compared to Tilapia mossambica and Mystus vittatus, which showed lipid contents of 2.86% and 2.25%, respectively. Conversely, carbohydrate content was highest in Katelysia opima (5%) compared to Tilapia mossambica and Mystus vittatus, which contained 2.3% and 2.7% carbohydrates, respectively. Overall, Katelysia opima exhibited high lipid and carbohydrate content, whereas protein content is comparable to Tilapia mossambica and Mystus vittatus.